Freedom of Expression in the Digital Age: Can Hacking Government Websites Be Justified? - Saputra, Ricky (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2023)
In today’s internet era, hacking the official government website has become a controversial event that raises questions about the limits of freedom of expression. This article examines the debate surrounding the hacking of government websites as a form of online expression. In the virtual world, individuals or groups can express their opinions, express their dissatisfaction, or criticize the government. However, the hacking of official government websites has become something interesting to discuss. In situations where groups or individuals convey their messages or protest online, these actions can be regarded as a form of freedom of expression. On the other hand, it can be seen as a threat to cybersecurity and the integrity of government institutions. This research aims to give a better understanding of the complexity of the problem by dealing with it from different perspectives. It also aims to provide a basic understanding for a deeper discussion of the limits of freedom of expression in the virtual world. The results of this research are expected to help the parties involved in making policies, which allow people to speak online while maintaining the cybersecurity and the integrity of government agencies.